2013
DOI: 10.1002/smll.201301617
|View full text |Cite
|
Sign up to set email alerts
|

Grafting Single Molecule Magnets on Gold Nanoparticles

Abstract: The chemical synthesis and characterization of the first hybrid material composed by gold nanoparticles and single molecule magnets (SMMs) are described. Gold nanoparticles are functionalized via ligand exchange using a tetrairon(III) SMM containing two 1,2-dithiolane end groups. The grafting is evidenced by the shift of the plasmon resonance peak recorded with a UV–vis spectrometer, by the suppression of nuclear magnetic resonance signals, by X-ray photoemission spectroscopy peaks, and by transmission electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 54 publications
6
31
0
Order By: Relevance
“…Best simulations21 of the spectra were obtained by using S =13/2, D =−0.318(4) cm −1 , E <0.006 cm −1 , g x,y =2.010(5) and g z =2.040(5), while no evident effect of the presence of the axial fourth‐order term could be found. It is evident that a residual contribution from traces of Fe 4 is present, clearly witnessed by a parallel transition at 1 kOe 7. 22 Notwithstanding this impurity, the obtained values confirm the easy axis nature and the very small rhombicity of the Fe 3 V system, in agreement with the close‐to‐axial symmetry of the molecule.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Best simulations21 of the spectra were obtained by using S =13/2, D =−0.318(4) cm −1 , E <0.006 cm −1 , g x,y =2.010(5) and g z =2.040(5), while no evident effect of the presence of the axial fourth‐order term could be found. It is evident that a residual contribution from traces of Fe 4 is present, clearly witnessed by a parallel transition at 1 kOe 7. 22 Notwithstanding this impurity, the obtained values confirm the easy axis nature and the very small rhombicity of the Fe 3 V system, in agreement with the close‐to‐axial symmetry of the molecule.…”
Section: Resultssupporting
confidence: 60%
“…[5] In particular, homometallic iron(III) derivatives, despite the weak anisotropy introduced by high-spin d 5 ions, have led to the first observation of magnetic hysteresis from SMMs deposited on a conducting substrate such as a flat gold surface [6] or gold nanoparticles. [7] However, as the blocking of the magnetization in such molecules occurs below 1 K, experiments on tetrairon(III) systems are extremely demanding. Moreover, fast relaxation in zero field owing to tunneling of the magnetic moment prevents the observation of a significant remnant magnetization in randomly oriented samples.…”
Section: Introductionsupporting
confidence: 46%
See 1 more Smart Citation
“…To obtain independent information on magnetic anisotropy, we also recorded W‐band EPR spectra on microcrystalline powder of 2 at 40 K (Figure ). The spectrum shows the typical features observed in several Fe 4 compounds measured at this frequency . Of particular relevance for the determination of the axial zfs parameter D is the low‐field transition, assigned to the M S =−4→ M S =−3 resonance .…”
Section: Resultsmentioning
confidence: 74%
“…Moreover, characterising the magnetic properties of an SMM on a surface usually requires highly sensitive synchrotron‐based techniques because of the tiny quantities of sample present in a mono‐ or even multi‐layer. However, some of us reported that appropriately functionalised Fe 4 SMMs could be immobilised on monodisperse Au nanoparticles (NPs), and that the resulting hybrid material could be characterised by standard SQUID (superconducting quantum interference device) methods . Murugesu and co‐workers instead attached Dy 2 SMMs to “naked” gold NPs of a wide range of sizes (generated by laser ablation), then studied them by standard methods, revealing a more pronounced change in the magnetisation dynamics …”
Section: Figurementioning
confidence: 99%